Pertanian yang Selaras dengan Alam di Siborong-Borong : Inspirasi dari Kitab Suci - Tickos Elia Siahaan; Raja Pangihutan Sitompul; Veronika Tumangger (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research investigates sustainable agricultural activities that incorporate spiritual values ​​from holy books in Siborong-Borong, North Tapanuli. Agriculture is seen as a form of worship as well as an environmental obligation, with an emphasis on organic techniques oriented towards sustainability. The case study in Wongaya Betan shows the success of agroecology in increasing crop yields without damaging the environment. A qualitative method with a case study approach was applied, involving observations and interviews with local farmers. Research findings emphasize the importance of training, the use of organic fertilizer, the integration of agriculture and animal husbandry, and human responsibility as stewards of the earth. Spiritual values ​​provide an ethical basis for fairer and more sustainable agricultural practices.